CREATIVE PROJECT (EXPERIENCE OF TOMSK POLYTECHNIC UNIVERSITY) - Inna V. Plotnikova; Ludmila A. Red’Ko; Marina N. Yanushevskaya (Высшее образование в России, 2016)
The empirical basis of the article is a practical experience in implementing creative projects under the CDIO Initiative at Tomsk Polytechnic University for 2 years (4 semesters) in training bachelors majoring in «Quality Management». The implemented projects are considered, and the obtained project results are analyzed and summarized. RecomA mendations to provide pedagogical conditions to implement project activities in undergraduate training are suggested.